The acute effects of different whole-body vibration amplitudes and frequencies on flexibility and vertical jumping performance - Gerodimos, V.; Zafeiridis, A.; Karatrantou, K.; Vasilopoulou, T.; Chanou, K.; Pispirikou, E. (Journal of Science and Medicine in Sport, 2010)
Frequency and amplitude determine the training load of whole-body vibration (WBV) exercise and thereby possible neuromuscular adaptations. We investigated the effects of amplitude and frequency of a single bout of WBV on flexibility and squat jump performance (SJ) and the time-course of these effects. In the amplitude study, twenty-five females performed three vibration protocols (VPs) for 6 min at frequency of 25 Hz and amplitudes of 4 mm, 6 mm, and 8 mm and one control protocol (CP). In the frequency study, eighteen females performed three VPs at 6 mm amplitude and frequencies of 15 Hz, 20 Hz, and 30 Hz and one CP. Flexibility and SJ were measured before, immediately-post and 15 min recovery. All protocols were performed on a side-to-side alternating vibration plate. In the amplitude study, flexibility was improved (p < 0.01) immediately-post in VP4, VP6, VP8 (31.8 ± 8.2, 31.9 ± 7.6, 31.5 ± 7.9, respectively) and at 15 min recovery (31.6 ± 8.1, 31.5 ± 7.9, 31.0 ± 8.2, respectively) vs. pre-vibration (30.2 ± 8.6, 30.3 ± 8.1, 30.2 ± 8.3, respectively), but remained unchanged in CP (30.6 ± 8.3 immediately-post, 30.7 ± 8.2 at 15 min vs. 30.4 ± 8.2 pre-vibration). In the frequency study, flexibility was improved (p < 0.01) immediately-post in VP15, VP20, VP30 (31.5 ± 5.2, 31.3 ± 5, 31.7 ± 5.3, respectively) and at 15 min recovery (31.3 ± 5.4, 31.3 ± 5.0, 31.3 ± 5.3, respectively) vs. pre-vibration (30.6 ± 5.4, 30.2 ± 5.7, 30.3 ± 5.9, respectively), but not in CP (30.7 ± 5.1 immediately-post, 30.6 ± 5 at 15 min vs. pre-vibration 30.5 ± 5.7). There were no significant effects of amplitude or frequency on SJ. In conclusion, a single WBV bout using a side-to-side alternating vibration plate may increase flexibility which persists for at least 15 min, without altering jumping performance. These effects were observed irrespective of frequency and amplitude.